2016
DOI: 10.1108/ribs-02-2016-0011
|View full text |Cite
|
Sign up to set email alerts
|

Quality of financial reporting in the Asia-Pacific region

Abstract: Purpose The main purpose of this paper is to examine the causes and interrelations between ownership composition and financial reporting quality of firms in the Asia-Pacific region. Design/methodology/approach The study uses panel data for 420 firms for the period 2011-2013 (three years) from Australia, Singapore, Malaysia, the Philippines and Pakistan. Findings Overall, the authors find that ownership concentration is positively associated with the financial reporting quality. However, institutional owner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 88 publications
5
31
1
Order By: Relevance
“…In Iran, Mehrani et al (2017) found significant and positive association among IO and high earnings quality. Similar results were reached by Yasser et al (2016) who examined the relationship between ownership structure and quality of financial reporting in Asia-Pacific region. The results indicated that Institutional as well as foreign ownership are associated with improved financial disclosure in developing countries.…”
Section: Literature Review and Hypothesis Developmentsupporting
confidence: 76%
See 1 more Smart Citation
“…In Iran, Mehrani et al (2017) found significant and positive association among IO and high earnings quality. Similar results were reached by Yasser et al (2016) who examined the relationship between ownership structure and quality of financial reporting in Asia-Pacific region. The results indicated that Institutional as well as foreign ownership are associated with improved financial disclosure in developing countries.…”
Section: Literature Review and Hypothesis Developmentsupporting
confidence: 76%
“…Most prior studies focused on the percentage of shares held by institutional investors and the concentration of their ownership on quality of disclosure (for instance, Jiang et al, 2011;Boone and White, 2015;Yasser et al, 2016;Hsu et al, 2016;Shiri et al, 2016). However; the effect of institutional investors on FLI disclosure level has been overlooked.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies advocate that foreign ownership should encourage firms to be better prepared for IFRS adoption ( Guerreiro et al., 2012 ). Some other studies state that foreign ownership has a positive relationship with financial disclosure ( Yasser et al., 2016 ), enhances their financial reporting quality ( Lee et al., 2013 ), is more timely recognition of economic gains ( Bagaeva, 2008 ), and increases financial statement comparability based on IFRS ( DeFond et al. , 2011 a).…”
Section: Review Of Literaturementioning
confidence: 99%
“…So, this study used an extended Value-Added Intellectual Coefficient method (eVAIC). eVAIC = {Value Added /Human Capital + (Relational Capital/Value Added + Innovation Capital/Value Added + Process Capital/Value Added)} + Value Added/Capital Employed Discretionary revenues method is used to measure financial reporting quality (Yasser et al, 2016;Stubben, 2010). GFC is a dummy variable.…”
Section: Methodsmentioning
confidence: 99%